“Estudio de la diversidad de hongos micorrízicos arbusculares nativos y su potencial micorrízico en el cultivo de café (coffea arabica L.) en diferentes condiciones agroecológicas de la región San Martín” - Coral Ruiz, Laura (2015)
The research aimed to determine the diversity of mycorrhizal fungi and mycorrhizal Arbusculares Native potential in growing coffee (Coffea arabica L.) in different agroecological conditions of the region San Martín "to this coffee farms they were selected in three provinces (Lamas, Moyobamba and El Dorado) on each farm three altitudes (A 1 = 800-1000, A2= 1000-1200, A3= 1200-1400 m.s. n. m. m) were located using three varieties of coffee (Pache, Caturra and National) of which biological samples of soil and roots were collected, each soil sample a physical-chemical analysis was performed, evaluation of ecological parameters (density of spores, morphological richness, relative abundance and frequency of isolation) was also performed. to the samples Root was evaluated the percentage of colonization of fungí arbuscular mycorrhizal native and finally was made a linear correlation analysis of the percentage of colonization, ecological parameters and soil. In the results, the province of Lamas presented the highest values of density of spores (2055 spores/1 O g soil) and morphological wealth (27 morphotypes/sample evaluated) also the highest percentage of colonization (12.7-20.0%) in the roots of coffee plants; on the other hand it was found that there is positive correlation between the percentage of colonization and ecological parameters, but negatively correlated with pH, soil nitrogen and phosphorus. Keywords: Mycorrhizal fungi, Spores, Varieties and Altitudes.